Fire in East Kalimantan: a panoply of practices, views and (discouraging) effects - Colfer, C.J.P. (2001)
This paper describes 1999 research intended to shed light on the causes and effects of the devastating 1997-98 forest fires in East Kalimantan. The author visited six communities and interviewed representatives of several other stakeholders (oil palm plantations, industrial timber plantations, timber companies, local government officials) about the causes and effects of the fires. She describes the traditional fire management techniques known by the Kenyah (a dayak group) in several locations. The fires varied considerably in intensity and damage done, among the communities. But some sustained very severe damage to their environment and suffered serious health consequences (both physical and psychological). The paper concludes by estimating the relevance of ten propositions relating to the likelihood of fire danger to each of the six villages visited.